Repetitive transcranial magnetic stimulation as an adjunct to quadriceps strengthening exercise in knee osteoarthritis: a pilot randomised controlled trial - Wei-Ju Chang; Siobhan M Schabrun; Sam Adie; Justine M Naylor; Rodrigo R N Rizzo; Nahian Chowdhury; Harrison Finn; Edel O’Hagan; Alan Chiang; Edward Gorgon (BMJ Open)
Objective To examine the feasibility, safety and perceived patient response of a combined repetitive transcranial magnetic stimulation (rTMS) and quadriceps strengthening exercise intervention for knee osteoarthritis.Methods A two-arm, participant-blinded, therapist-blinded and assessor-blinded, randomised controlled trial with additional follow-up of pain and function at 3 months. Participants were randomised to receive active rTMS+exercise (AR+EX) or sham rTMS+exercise (SR+EX) twice weekly for 6 weeks while completing home exercises twice a week. Primary outcomes included recruitment rate, treatment attendance, dropouts, willingness to undergo therapy (11-point Numeric Rating Scale, ‘not at all willing’=0 and ‘very willing’=10), success of participant, therapist and outcome assessor blinding, adverse events and Global Perceived Effect Scale. Secondary outcomes were pain, function and measures of physiological mechanisms.Results 86 people were screened, 31 (36%) were randomised, 28 (90%) completed the treatments and 3 (10%) dropouts at 3-month follow-up. Both groups had high treatment attendance (98.4% and 100%). All participants scored at least 7 on the willingness to undergo therapy scale. Blinding was successful. No adverse events were reported. At the postintervention assessment, 80% in the AR+EX group and 75% in the SR+EX group reported an improvement on the Global Perceived Effect Scale. Both groups demonstrated within-group improvements in pain at the postintervention assessment but not at the 3-month follow-up. Function improved only in the AR+EX group at the postintervention assessment.Conclusions Combined rTMS and quadriceps strengthening exercise intervention for knee osteoarthritis is feasible, safe and well-received. A full-scale trial is justified to assess the clinical benefits of this novel treatment.Trial registration number ACTRN12621001712897.